KONSEP-KONSEP KEPEMIMPINAN ISLAM DALAM MASYARAKAT - Muhammad Dzulfiqar, Muhammad Olifiansyah, Bimansyah Putra Dianying, Wahyu Hidayat (TARBIYA ISLAMIA : Jurnal Pendidikan dan Keislaman, 2020)
ABSTRACTProphet Adam AS as the first man on earth had the task of God as a fiduciary leadership. From Adam’s, the leadership process continues until the descent and his grandchildren, even to this day. Thus, the leadership of the laws that continue to prevail in the face of this earth. Therefore, in Islam urgency of leadership in the Muslim community is a necessity. Leadership process is basically a social phenomenon, because it takes place in the interaction between humans as social beings. Leadership can not be released to do with social situations that are formed and are taking place in society. Therefore it is always evolving social situations and can change, then none ways of acting that can be used in exactly the same in the face of two situations that look the same, especially for different situations in the community environment. Although leadership is important to be implemented, be a leader is not as easy as turning the palm of the hand. To learn more about leadership in the community, need to know about the basic concepts of leadership, especially in Islamic societies which include: the importance of leadership, for the emergence of a variety of leadership, leadership functions, forms of leadership, as well as the characteristics of the ideal leader in Islamic societies.Keywords: Leadership, Islamic societies